Behavioral Effects of a Novel Benzofuranyl-Piperazine Serotonin-2C Receptor Agonist Suggest a Potential Therapeutic Application in the Treatment of Obsessive–Compulsive Disorder - Rodriguez, Michelle M.; Overshiner, Carl; Leander, J. David; Li, Xia; Morrow, Denise; Conway, Richard G.; Nelson, David L.; Briner, Karin; Witkin, Jeffrey M. (Frontiers in Psychiatry, 2017)
Selective inhibitors of the neuronal uptake of serotonin (SSRIs) are the only effective pharmacological treatments for OCD. Nonetheless, their generally limited efficacy, side-effects, and delayed onset of action require improved medications for this highly prevalent disorder. Preclinical and clinical findings have suggested serotonin2C (5-HT2C) receptors as a potential drug target. Data in rats and mice are presented here on the effects of a novel 5-HT2C receptor agonist ((3S)-3-Methyl-1-[4-(trifluoromethyl)-7-benzofuranyl]-piperazine) (CPD 1) with high potency and full efficacy at 5-HT2C receptors and less potency and partial agonism at 5-HT2A and 5-HT2B receptors. Effects of CPD 1 on consummatory (schedule-induced polydipsia in rats) and non-consummatory behaviors (marble-burying and nestlet-shredding in mice) that are repetitive and non-habituating were studied. We also evaluated the effects of CPD 1 in rats with isoproterenol- and deprivation-induced drinking in rats to compare with the polydipsia studies. The SSRIs, fluoxetine and chlomipramine decreased the high rates of drinking in rats engendered by a schedule of intermittent food delivery (schedule-induced polydipsia). The effects of fluoxetine, but not of d-amphetamine, were prevented by the selective 5-HT2C receptor antagonist SB242084. The 5-HT2C receptor agonists Ro 60-0175 and CPD 1 also decreased drinking, but unlike the SSRIs and Ro 60-0175, CPD 1 dose-dependently decreased excessive drinking without affecting lever press responses that produced food. The effects of CPD 1 were prevented by SB242084. CPD 1 also suppressed drinking induced by isoproterenol and by water deprivation without affecting normative drinking behavior. CPD 1, like fluoxetine, also suppressed marble-burying and nestlet-shredding in mice at doses that did not affect rotorod rotarod performance or locomotor activity. The behavioral specificity of effects of CPD 1 against repetitive and excessive behaviors suggests a potential therapeutic application in OCD.